(untitled) - Burke, Billie; 1899-1979.; Haley, Jack; 1895-1967.; Lahr, Bert; 1890-1949.; Morgan, Frank; 1922-1969.; Garland, Judy; 1885-1970. (distributed by Warner Home Video, 2013)
The charming film based on the popular L.Frank Baum novel, Dorothy and her dog Toto, are caught in a tornados path and somehow end up in the land of Oz. Here she encounters some memorable friends and foes in her journey to meet the Wizard of Oz who everyone says can help her return home and possibly grant her new friends their goals of a brain, heart and courage.
Rating: G; general audiences: all ages.
CHV Rating: G.
Keywords: Juvenile films; Oz (Imaginary place); Juvenile films; Wizard of Oz (Fictitious character); Juvenile films; Juvenile films; Scarecrow (Fictitious character : Baum); Juvenile films; Tin Woodman (Fictitious character); Juvenile films; Gale, Dorothy (Fictitious character); Cowardly Lion (Fictitious character)